2008
DOI: 10.1016/j.addr.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-drug conjugates: Recent development in clinical oncology

Abstract: Targeted drug delivery aims to increase the therapeutic index by making more drug molecules available at the diseased sites while reducing systemic drug exposure. In this update, we provide an overview of polymer-drug conjugates that have advanced into the clinical trials. These systems use synthetic water-soluble polymers as the drug carriers. The preclinical pharmacology and recent data in clinical trials with poly(L-glutamic acid)-paclitaxel (PG-TXL) are discussed first. This is followed by a summary of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
239
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(247 citation statements)
references
References 60 publications
1
239
0
7
Order By: Relevance
“…Opaxio, in comparison with its conventional paclitaxel-based treatment, showed some safety-related advantages such as alopecia was rare, nausea and vomiting were uncommon and hypersensitivity reactions were rarely observed. A significant survival benefit has also been observed for women receiving Opaxio vs. paclitaxel [7]. These promising results have provided the confidence that PDCs can give therapeutic benefits in the field of oncology.…”
Section: Magnitude Of the Epr Effect In Different Tumour Typesmentioning
confidence: 87%
See 1 more Smart Citation
“…Opaxio, in comparison with its conventional paclitaxel-based treatment, showed some safety-related advantages such as alopecia was rare, nausea and vomiting were uncommon and hypersensitivity reactions were rarely observed. A significant survival benefit has also been observed for women receiving Opaxio vs. paclitaxel [7]. These promising results have provided the confidence that PDCs can give therapeutic benefits in the field of oncology.…”
Section: Magnitude Of the Epr Effect In Different Tumour Typesmentioning
confidence: 87%
“…Clinical trials have shown evidence of tumour responses to PDC to various degrees, and some conjugates (e.g., poly-L-glutamic acid (PGA)-paclitaxel) have progressed to Phase III trials [5,6]. In spite of several advantages of PDCs over the relevant parent drugs, such as a more favourable toxicity profile, superior quality of life and a significant survival rate [7], to date, no such conjugate has entered the market place, which suggests that system design and/or patient selection are still suboptimal.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been designated as an orphan drug in combination with radiotherapy for the treatment of glioblastoma multiforme (GBM) [86]. Polyglutamates are highly biocompatible, biodegradable and multifunctional polymers, which have been successfully used as building blocks in polymer-drug conjugates and polymeric micelles for various medical applications [4,14,25,87]. In the body, such degradability is triggered by cysteine proteases (particularly cathepsin B), which play a key role in the lysosomal degradation of this polymer [88].…”
Section: Drug Deliverymentioning
confidence: 99%
“…The most commonly used materials include PEG, ploy(lactic-co-glycolic) acid (PLGA), polylactic acid (PLA), and polycaprolactone (PCL). 6,7 Some polymer-based therapeutics, such as Zinostatin Stimalmer, Oncaspar PEG-L-asparaginase, and Neulasta PEG-GCSF, have been clinically approved for cancer treatment, while more formulations are undergoing clinical investigations. 7 Although these clinically approved nano-based treatments exhibit promising results with reduced hazard potential, they have some drawbacks.…”
mentioning
confidence: 99%